On standardization of basic datasets of electronic medical records in traditional Chinese medicine. (June 2019) - Zhang, Hong; Ni, Wandong; Li, Jing; Jiang, Youlin; Liu, Kunjing; Ma, Zhaohui
Highlights: This paper describes the work to standardize Traditional Chinese Medicine (TCM) medical records. The new standard was created through modification and augmentation of the existing western medicine medical record standard WS-445. In order to standardize Traditional Chinese Medicine (TCM) medical records, the TCM clinical information system was modeled with an outpatient clinical database structure and an inpatient clinical database structure. Based on the proposed models, eight new datasets were created to describe TCM clinical diagnosis and treatment activities. Some of the existing data elements from WS-445 are kept as is, some are expanded with new TCM contents, and yet some 732 brand new data elements are created to cover TCM specialties which do not have a proper counterpart in western medicine. The proposed new standard were verified with over 170, 000 medical records, and validated by three independent TCM hospitals. Abstract: Background and Objective: Standardization of electronic medical record, so as to enable resource-sharing and information exchange among medical institutions has become inevitable in view of the ever increasing medical information. The current research is an effort towards the standardization of basic dataset of electronic medical records in traditional Chinese medicine. Methods: In this work, an outpatient clinical information model and an inpatient clinical information model are created to adequately depict the diagnosis processes and treatment procedures of traditional Chinese medicine. To be backward compatible with the existing dataset standard created for western medicine, the new standard shall be a superset of the existing standard. Thus, the two models are checked against the existing standard in conjunction with 170, 000 medical record cases. If a case cannot be covered by the existing standard due to the particularity of Chinese medicine, then either an existing data element is expanded with some Chinese medicine contents or a new data element is created. Some dataset subsets are also created to group and record Chinese medicine special diagnoses and treatments such as acupuncture. Results: The outcome of this research is a proposal of standardized traditional Chinese medicine medical records datasets. The proposal has been verified successfully in three medical institutions with hundreds of thousands of medical records. Conclusions: A new dataset standard for traditional Chinese medicine is proposed in this paper. The proposed standard, covering traditional Chinese medicine as well as western medicine, is expected to be soon approved by the authority. A widespread adoption of this proposal will enable traditional Chinese medicine hospitals and institutions to easily exchange information and share resources.